2015
DOI: 10.1111/edt.12210
|View full text |Cite
|
Sign up to set email alerts
|

Custom‐Fitted EVA Mouthguards: what is the ideal thickness? a dynamic finite element impact study

Abstract: It was concluded that the use of a mouthguard promoted lower stresses and strains in teeth during an impact with a rigid object. There was no substantial difference in peak stresses and strains and in shock absorption among the different mouthguard thicknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
215
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(229 citation statements)
references
References 32 publications
5
215
1
8
Order By: Relevance
“…Tulunoglu and Ozbek 37 concluded that a mouthguard's thickness is the crucial factor to prevent injuries. The cheeks and lips have a natural protective function, 34 and the motion of the head may also play a role. As a layer thickness of more than 6 mm allegedly handicaps athletes, 20 only the labial part of the dentition, which is most exposed to impacts, should be protected by a layer thickness exceeding 6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Tulunoglu and Ozbek 37 concluded that a mouthguard's thickness is the crucial factor to prevent injuries. The cheeks and lips have a natural protective function, 34 and the motion of the head may also play a role. As a layer thickness of more than 6 mm allegedly handicaps athletes, 20 only the labial part of the dentition, which is most exposed to impacts, should be protected by a layer thickness exceeding 6 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Le plus communément utilisé est le copolymère EVA (Éthylène Vinyle Acétate) [39,40] pour sa capacité à absorber les chocs. Le silicone, le caoutchouc naturel, le polyuréthane et la résine acrylique sont moins utilisés [40].…”
Section: Différents Types De Pibunclassified
“…Si de nombreux facteurs influencent la capacité d'absorption des chocs d'une PIB (matériau utilisé pour sa fabrication, processus de fabrication, géométrie de la PIB), le plus important est son épaisseur [39,41]. Plusieurs études ont montré que la capacité d'absorption des chocs augmente avec l'épais-seur de la PIB [39,41].…”
Section: Critères Techniques De Fabricationunclassified
See 2 more Smart Citations